Long-term impact of Global Health educational experiences in Rome: an attempt of measurement - Giulia Civitelli; Gianfranco Tarsitani; Alessandro Rinaldi; Maurizio Marceca (BMC, 2020)
Abstract Background Global health education (GHE) is spreading in Europe and in other parts of the world. Since 2008, Sapienza University of Rome has offered activities to medical and other health profession students related to global health (GH), which is grounded in the theory of social determinants of health and inspired by social justice. The educational activities included elective courses as well as community and service-learning experiences, referred to as GH gyms. This study attempts to measure the long-term impact of these educational experiences, especially to demonstrate their influence on the perceived social responsibility of future health professionals. Methods A questionnaire was elaborated and tested on a small sample of participants. It was sent to participants by e-mail. Quantitative results were analysed through descriptive statistics and qualitative answers were carefully read and classified. Results A total of 758 students from different faculties took part to the educational experiences. Only 488 e-mail addresses were available. One hundred and five (21.5%) questionnaires were returned. Participation in GH gyms was perceived to have had a higher influence on future professional and personal choices, when compared to participation in elective GH courses. Conclusions The study shows that consideration of health and social issues related with inequities in health and the use of interactive teaching methodologies had important effects on social responsibility of a large number of students. As there could be a selection bias among respondents, more research is needed to understand the impact of GH educational experiences. The inclusion of global health education in health and social curricula and the use of interactive methodologies with a correct evaluation of results are the indications that emerge from this research, together with the necessity of a strong involvement of students, professors and the whole academic reality.